Hubungan Beban Kerja dengan Kepatuhan Pendokumentasian Keperawatan pada Penerapan SIMRS di IGD dan ICU RSUD Haji Makassar - Asti Puspitasari; Suriyani Suriyani; Syamsuddin Syamsuddin (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Nursing documentation is an essential part of healthcare services, playing a key role in communication, care continuity, and serving as legal evidence. The introduction of the Hospital Management Information System (SIMRS) aims to improve the efficiency of documentation processes. However, high workloads in critical areas such as the Emergency Department (IGD) and Intensive Care Unit (ICU) may influence nurse compliance with documentation protocols. This study investigates the relationship between workload and nursing documentation compliance during the implementation of SIMRS at RSUD Haji Makassar's IGD and ICU. A quantitative cross-sectional design was used, with 30 nurses participating (total sampling). The workload was assessed using the NASA Task Load Index (NASA-TLX), while compliance was evaluated through a questionnaire. The data were analyzed using Chi-Square and Fisher’s Exact Test. The results showed that the majority of respondents experienced heavy workloads (83.3%), and most had compliant documentation (96.7%). However, the statistical analysis yielded a p-value of 1.000, indicating no significant relationship between workload and documentation compliance. Based on these findings, the study recommends optimizing SIMRS usage and providing ongoing training to ensure improved compliance with nursing documentation practices.